L’intervention féministe sous l’influence de l’intersectionnalité : enjeux organisationnels et communicationnels au sein des organismes féministes au Québec - Isabelle Marchand; Christine Corbeil; Carole Boulebsol (Communiquer)
In Quebec, feminist intervention was spread significantly in the mid-1970s and presented itself as a therapeutic and political alternative to traditional therapies in the field of mental health and the fight against gender-based violence, to support women and defend their rights. It is based, among other things, on individual and collective awareness and empowerment in a society marked by gender discrimination. More recently, the popularity of intersectionality, as a framework for theoretical, political and practical analysis, has led francophone feminist practitioners to take a critical look at their approaches and postures, in particular by considering the interweaving of sexism with other forms of oppression such as racism. Based on several studies caconducted in recent years with practitioners, the authors propose to reflect on the recent development of feminist intervention under the influence of intersectionality. This article suggests some analysis of the organizational and relational issues with which groups and workers must deal with in a complexe social and intervention context.